A Web‐based open source tool for Toxicokinetic and Toxicodynamic modelling. Issue 11 (13th November 2020) - Bossier, Han; Chau, Joris; Ndour, Cheikh; Varewyck, Machteld; Verbeke, Tobias; Vergucht, Stephanie
Abstract : This report presents the implementation of a web tool for the extension of exposure‐and toxicokinetic‐toxicodynamic analysis that has been developed under aspecific EFSA request to Open Analytics under the framework agreement (OC/EFSA/AMU/2015/02).An open source software has been developed in R as a WEB‐based tool including different components for the modelling of toxicokinetic (TK) and toxicodynamic (TD) processeswithin a structuredworkflow. The workflow provides the steps to perform such TK‐TD modelling for single chemicals in the human health, animal health and ecological risk assessment. The web‐based tool results in the implementation of four modules: (1) Chemical specific modules, (2) Physiological and life cycle trait modules, (3) Toxicokinetic module, and (4) Toxicodynamic module.